If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(6+c)=4(c-6)
We simplify the equation to the form, which is simple to understand
5(6+c)=4(c-6)
Reorder the terms in parentheses
+(+30+5c)=4*(c-6)
Remove unnecessary parentheses
+30+5c=+4+*(+c-6+)
Reorder the terms in parentheses
+30+5c=+(+4c-24)
Remove unnecessary parentheses
+30+5c=+4c-24
We move all terms containing c to the left and all other terms to the right.
+5c-4c=-24-30
We simplify left and right side of the equation.
+1c=-54
We divide both sides of the equation by 1 to get c.
c=-54
| 56d^2-8d=0 | | -2X+8=4 | | 7z+2=-19 | | .8x^2+8x+19=0 | | 30+n=11 | | 4x+-12=-4 | | 4x+-12=4 | | -1+14x= | | 0.50x+0.20(40)=0.25(76) | | 8d-(25)=3d | | 4000g=48000 | | 0=-16x^2+9x+46 | | 7(w-4)=28 | | -4(x+7)+3=-25 | | 8x^2+8x+16=0 | | (m+8)(m-15)=0 | | -7=4 | | 7x+-5=-19 | | 144=7r-5r | | -7=4b | | 8x^2+11x+19=0 | | x^2+y^2+20x-8y+35=0 | | n^2+8n+3=0 | | 16-7d=(-3d)+2 | | 3x-4y=9 | | 5(2x-3)=27+3x | | 3x^2-24x+21=0 | | 1.4m=1.5m-0.57 | | -5x+6=16 | | 1.4(5x-0.3)= | | =1.4(5x-0.3) | | -5+6=16 |